“Evaluación de cuatro dosis de microorganismos eficientes en rendimiento productivo del cultivo de pepinillo (cucumis sativus L.) en la provincia de Lamas- San Martín” - Bocanegra Villanueva, Ana Silvia (2014)
This paper titled "Evaluation of four doses of microorganisms efficient yield of cucumber crop (Cucumis sativus L.) in the Province of Lamas - San Martin, were to: determine the optimal dose of beneficia! microorganisms in the Stonewall growing F1 hybrid cucumber and determine the economic analysis of the study treatments. The present research was conducted in the Horticultura! Fundo "The Pacific", which is located in the district of Lamas, Lamas Province and Department of San Martín. The main access road is the road the Femando Belaunde Terry - North at 22 km from Tarapoto, whose coordinates are: Latitude South 06 ° 20 '15 West Longitude 76 ° 30' 45 "at an altitude of 835 msnmm. To carry out this research we used the statistical design of randomized complete block (RCBD) with 5 treatments and 4 replications. Microorganisms were evaluated efficient dose of 2, 3, 4 and 5 l.ha-1 with a control. The variables evaluated were: plant height, number of flowers per plant, number of flowers, number of fruit per plant, fruit length, fruit diameter, percentage of fruit set, fruit yield in cientos.ha-1 and economic analysis of the treatments studied. The most significant findings were: T4 treatments (51 /ha of EM) and T2 (3 l.ha-1 of EM) obtained the highest average in fruit yield hundreds of frutos.ha-1 with an average of 8189.1 hundred frutos.ha-1 and 7962.5 cientos.ha fruit yield in respectively; performance evaluation of fruit cientos.ha-1, the percentage of fruit set and fruit diameter positive linear responses described in terms of increased applications of EM doses; higher profits were obtained in treatments T4 (5.0 1 organisms.ha-1 ) and T3 (4.0 1 organisms.ha-1 ) with S /. 59 621.07 and 58 900.00 and benefit I cost of 3.63 and 3.60 respectively. Keywords: microorganisms efficient, optima! dose, yield, fruit set